Pengaruh Pelatihan Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Di Kantor Kelurahan Setia Asih Kecamatan Tarumajaya - Hasna Dwiyanti; Novita Wahyu Setyawati; Indah Rizki Maulia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to determine and analyze the effect of Job Training and Work Discipline on Employee Performance at the Setia Asih Subdistrict Office, Tarumajaya District. This type of research is quantitative. The sample used was 35 respondents from Setia Asih Village, Tarumajaya District. To test and prove the research hypothesis using the SPSS version 26 application. The results of the research that has been carried out are that the independent variables have a positive and significant effect on the dependent variable. Based on the test results and data analysis for the Job Training variable, it was obtained that the t-value was 2.489 > 1.692 (t-table) with a sig of 0.018 < 0.05, meaning that Job Training (X1) had a positive and significant effect on Employee Performance (Y). Then the Work Discipline variable obtained a t-count value of 4.008 > 1.692 (t-table) with a sig of 0.000 < 0.05, which means that Work Discipline (X2) has a positive and significant effect on Employee Performance (Y) and it is known that the f-count is 18.930 > 3.295 (Ftable) with a sig value of 0.000 < 0.05 that simultaneously Job Training (X1) and Work Discipline (X2) have a positive and significant effect on Employee Performance (Y).